2019
DOI: 10.14715/cmb/2019.65.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside compound K inhibits growth of lung cancer cells via HIF-1α-mediated glucose metabolism

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related deaths. Compound K, an active metabolite of ginsenosides, is reported to exhibit anti-cancer property in various types of human malignancies. The present study investigated the role of compound K on glucose metabolism in NSCLC cells and its underlying mechanism. Our study found that compound K dose-dependently inhibited the cell viability of NSCLC cells. Moreover, administration with compound K decreased glucose uptake and lactate secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Furthermore, the suppression of the growth of NSCLC cells was studied by targeting the metabolism of glucose. Compound K suppressed the levels of hypoxia-inducible factor 1-alpha and its downstream glucose transporter1 gene [ 83 ]. Another study showed the anti-cancer effect of CK against HepG2 cells and xenografted (HepG2) BALB/c nude mice.…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…Furthermore, the suppression of the growth of NSCLC cells was studied by targeting the metabolism of glucose. Compound K suppressed the levels of hypoxia-inducible factor 1-alpha and its downstream glucose transporter1 gene [ 83 ]. Another study showed the anti-cancer effect of CK against HepG2 cells and xenografted (HepG2) BALB/c nude mice.…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…For example, Chen et al found that inhibiting the expression of HIF-1α decreased the GLUT1 expression level, and thus caused a reduction of the tumor volume and weight of LOVO cell line xenografts [42]. Some studies also have proposed that combined inhibition of HIF-1α and GLUT1 could be a promising cancer therapeutic strategy [43][44][45][46]. Our work demonstrated that PDQ is just one of the rst choice drugs that realize this antitumor effect.…”
Section: Discussionmentioning
confidence: 54%
“…which is associated with cancer cells proliferation and poor prognosis in tumors [9,10]. Studies have shown that ginsenoside can inhibit the growth of liver or lung cancers by inhibiting hypoxia-inducible factor-1α (HIF-1α) mediated glucose metabolism [11,12]. With the deepening of research, it is found that secondary ginsenosides and aglycones produced by degradation of ginsenosides have stronger pharmacological effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the high energy requirements of enhanced proliferation, cell division also requires large amounts of biomolecules, including nucleic acids and lipids, for which glucose is an important biosynthetic precursor. Enhanced levels of glucose transporters and enzymes in the glycolytic pathway and upregulated lactate level are often found in NSCLC cells, and inhibition of aerobic glycolysis arrests cancer cell proliferation ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%